2015
DOI: 10.1371/journal.pntd.0003812
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension and Skin Allergy Are Risk Factors for Progression from Dengue to Dengue Hemorrhagic Fever: A Case Control Study

Abstract: BackgroundCurrently, knowledge does not allow early prediction of which cases of dengue fever (DF) will progress to dengue hemorrhagic fever (DHF), to allow early intervention to prevent progression or to limit severity. The objective of this study is to investigate the hypothesis that some specific comorbidities increase the likelihood of a DF case progressing to DHF.MethodsA concurrent case-control study, conducted during dengue epidemics, from 2009 to 2012. Cases were patients with dengue fever that progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
1
25
2
2
Order By: Relevance
“…Sixteen articles, describing studies conducted from 2002 to 2012 met the eligibility criteria [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All studies included in the analysis were observational studies: nine retrospective cohort studies [ 12 , 15 , 18 , 20 , 21 , 22 , 23 , 26 , 29 ] and seven case-control studies [ 16 , 17 , 19 , 24 , 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen articles, describing studies conducted from 2002 to 2012 met the eligibility criteria [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All studies included in the analysis were observational studies: nine retrospective cohort studies [ 12 , 15 , 18 , 20 , 21 , 22 , 23 , 26 , 29 ] and seven case-control studies [ 16 , 17 , 19 , 24 , 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the clinical comorbidities of DF or DHF patients, the study results indicated that old age, hypertension, and diabetes were significantly correlated with the development of DHF (Table 3). Hypertension and diabetes are two important comorbidities that have been reported to correlate with DHF previously (Htun et al, 2015;Teixeira et al, 2015). Hypertension prompts vascular damage and endothelial dysfunction, inducing inflammatory activation of the endothelium, and altering the regulation of vascular tone and flow.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive individuals often have elevated C-reactive protein levels in the blood, which increases capillary permeability and risk of coagulopathy [17]. In Kerala State, India, patients with underlying hypertension were found to be 44 times more likely to die from dengue [11].…”
Section: Diabetes and Hypertension: Ncds That Worsen Clinical Outcomementioning
confidence: 99%